Responsabilidade social corporativa, governança corporativa e estrutura de propriedade: uma análise da empresa brasileira - Forte, Hyane Correia (2020)
The relationship between company and society must be considered beside the interaction with shareholders. The company's stakeholders, legitimately, have the right to be taken into account in their decision-making process. In this context, the corporate governance system must evolve to be able to make a company’s executives respect the rights of all stakeholders. In turn, it has been verified that the ownership structure plays an important role in the elaboration of company policies, with possible reflexes in the relationship with the set of stakeholders. The concentration of ownership has been shown to interfere in this process, in addition to being relevant in the alignment of interests between ownership and management. The aim of this paper is to investigate the effect of corporate governance and ownership structure on the level of corporate social responsibility in Brazilian companies. The sample was composed of 81 companies listed on B3 S.A. - Brasil, Bolsa, Balcão, in the period 2010-2018, totaling 631 annual observations. Corporate social responsibility was operationalized through the CSRHub agency's CSR index. Corporate governance was measured using the corporate governance index, established by Brandão and Crisóstomo (2015). Descriptive statistics of the data, ANOVA, Tukey-Kramer Post-Hoc Test, T-test, Pearson correlation and multiple linear regression using the Generalized Least Squares (GLS) and Ordinary Least Squares (OLS) methods were performed. The results indicate that corporate governance positively influences the extent of corporate social responsibility. The application of good corporate governance practices signals a better communication between the company and the various stakeholders. Thus, adherence to the best corporate governance practices can expand the strategic vision of management, affecting the establishment of CSR policies. The findings also show that the concentration of ownership positively influences the extent of corporate social responsibility of Brazilian companies. This result indicates that corporations with concentrated ownership are more likely to favor CSR actions, since the majority shareholders have their names strongly linked to the organization. Therefore, shareholders with power tend to make decisions aimed at CSR actions, seeking to raise the image and reputation of the company, so that they can raise their personal image.